PENGELOLAAN DAN POTENSI HUTAN RAKYAT BERBASIS PINUS (Pinus merkusii) BAGI PENDAPATAN PETANI DI KECAMATAN NGRAYUN KABUPATEN PONOROGO - Indah Anjar sari; Tatik Suhartati; Sugeng Wahyudiono (Tengkawang : Jurnal Ilmu Kehutanan, 2022)
Community forests in Ngrayun District are dominated by pine (Pinus merkusii) mixed with various perennials, Multi-Purpose Tree Species (MPTS), and food crops managed with different cropping patterns. The importance of knowledge management and potential as input for farmers to increase farmers' income. This study aimed to determine pine-based community forests' management characteristics and potential for farmers' income in the Ngrayun District. This research was conducted by interviewing 36 farmers who met the criteria using a questionnaire guide, field inventory using measuring plots measuring 20 m x 20 m, and secondary data on sap yields from the Forest Farmers Group (KTH). The data analysis used is descriptive analysis supported by quantitative data. The results showed that planting consisted of pure, mixed trees along the border and random mixture cropping patterns. Pine maintenance is pruning branches and renewal of koakan every 3-5 days—the sap harvesting at the time of koakan renewal and a few days before sap weighing. Rubber marketing through KTH collaborates with CV Rimbun Sejahtera and CV Pinus Mulyo. The highest potential for pure pine pattern is 347.25 m3/ha, with sap yields of 78.56 kg/month with an income of Rp 707.040./month, and the lowest is mixed trees along the border with sap yield of 18.42 kg/month, and the monthly income Rp. 165.780.  It can be concluded that the management and potential of community forests affect farmers' incomes.Keywords: Community Forest, Income, Management, Pine, PotentialAbstrakHutan rakyat di Kecamatan Ngrayun didominasi oleh pinus (Pinus merkusii) yang dicampur dengan berbagai jenis tanaman keras, Multy Purpose Tree Spesies (MPTS) serta tanaman pangan yang dikelola dengan berbagai pola tanam. Pentingnya mengetahui pengelolaan dan potensi sebagai masukan bagi petani agar dapat meningkatkan pendapatan petani.  Tujuan penelitian ini untuk mengetahui karakteristik pengelolaaan dan potensi hutan rakyat berbasis pinus bagi pendapatan petani di Kecamatan Ngrayun. Penelitian ini dilakukan dengan mewawancarai 36 petani  yang memenuhi kriteria menggunakan panduan kuisioner, inventarisasi dilapangan menggunakan petak ukur berukuran 20 m x 20 m, dan data sekunder hasil getah dari Kelompok Tani Hutan (KTH).  Analisis data yang digunakan yaitu analisis deskriptif didukung data kuantitati. Hasil penelitian menunjukkan pengelolaan hutan rakyat penanaman terdiri pola tanam murni, campuran, trees along border dan random mixture. Pemeliharaan pinus yaitu pemangkasan cabang, pembaharuan koakan 3 – 5 hari sekali. Pemanenan getah saat pembaharuan koakan dan beberapa hari sebelum penimbangan getah. Pemasaran getah melalui KTH yang bekerjasama dengan CV Rimbun Sejahtera dan CV Pinus Mulyo. Potensi pinus paling tinggi pola murni 347,25 m3/ha hasil getah 78,56 kg/bulan dengan pendapatan Rp 707.040/bulan dan terendah pola trees along border 152,81 m3/ha hasil getah 18,42 kg/bulan dengan pendapatan Rp 165.780/bulan. Hal ini menunjukkan pengelolaan dan potensi hutan rakyat mempengaruhi pendapatan petani.Kata kunci: Hutan Rakyat, Pendapatan, Pengelolaan, Pinus, Potensi